PENGEMBANGKAN LEARNING COMMUNITY SISWA KELAS X SMK MELALUI PENERAPAN MODEL PEMBELAJARAN STAD BERBASIS CTL PADA PEMBELAJARAN DASAR ELEKTRONIKA - Yulianto, Adi (Edu Elektrika Journal, 2014)
This study aims to describe the application of CTL-based learning model STAD, develop community learning, and improve student learning outcomes in class X AV 1 SMK N 4 Semarang. This study was conducted in three cycles. Material each cycle is different but still within the power dynamic subject. Each cycle consists of planning, implementation, observation, and reflection. Community learning outcome data, affective and psychomotor learning outcomes derived from the observation sheet, cognitive learning outcomes obtained from the evaluation sheet. The results showed increased learning outcomes and the development of learning community class X AV 1 SMK N 4 Semarang after application of CTL-based learning model STAD on the subject of dynamic power.